1990
DOI: 10.2307/1963264
|View full text |Cite
|
Sign up to set email alerts
|

Defense Expenditures, Economic Growth, and the “Peace Dividend”

Abstract: ecent developments in Eastern Europe have created expectations of a "peace dividend" associated with reduced levels of U.S. defense expenditures. We present and empirically estimate a two-equation model for assessing the direct and indirect, immediate and delayed effects of changes in defense spending on economic growth in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(70 citation statements)
references
References 27 publications
1
64
0
5
Order By: Relevance
“…For Asia and Latin America, Murdoch et al (1997) found that defense expenditures positively affect economic growth. Many other studies have also found positive relationship between defense expenditures and economic growth (Lipow and Antinori, 1995;Ward and Davis 1992;Mintz and Huang, 1990;Deger, 1986;Deger and Smith, 1983).…”
Section: Defense Spending Affects Economic Growth Positivelymentioning
confidence: 87%
“…For Asia and Latin America, Murdoch et al (1997) found that defense expenditures positively affect economic growth. Many other studies have also found positive relationship between defense expenditures and economic growth (Lipow and Antinori, 1995;Ward and Davis 1992;Mintz and Huang, 1990;Deger, 1986;Deger and Smith, 1983).…”
Section: Defense Spending Affects Economic Growth Positivelymentioning
confidence: 87%
“…Negative effects of military expenditure on economic growth were found when alternative channels were investigated like through reducing the savings rate, crowding out investment in new capital stock, health and education and increasing tax burden with greater impact on resource restraint countries (see e.g. Smith, 1980;Cappelen et al, 1984;Mintz and Huang (1990), Huang and Mintz (1991), and Ward and Davis (1992), Batchelor et al, 2000;Dunne et al, 2001). Finally, there is another group of studies that imply that there is no relationship between the two variables mainly when the military expenditures are low (see e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Mintz and Stevenson (1995) first argued, the diversity of results is mainly as a result of the use of alternative channels of interaction between the two magnitudes and the research methodology. On that front, there are studies that focus on one country (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Benoit seemed to find a positive effect of the share of military expenditure on growth, but subsequent works failed to confirm this relationship across the world. The large subsequent literature does not seem to indicate any robust empirical regularity, with the exception of cases such as the EU (Kollias et al 2004); former USSR states (McDonald and Eger 2010); and the USA (Mueller and Atesoglu 1993;Atesoglu 2002), whether positive or negative as noted by Mintz and Stevenson (1995). Separately from the defense literature listed above, there also has been a revival of interest among economists in the determinants of growth prompted by the availability of the international data sets.…”
Section: Defense Expenditure and Economic Growthmentioning
confidence: 99%